Factors influencing perception of Work-Related Upper Limbs Disorders (WRULDs) among Malaysian women assembly workers - Abdullah, Haslinda; Zulkifli, Normaziah; Ma’rof, Aini Azeqa (Human Resource Management Academic Research Society, 2021)
Introduction: This paper attempts to discuss the contributions of individual factors toward the perception of Work Related Upper Limbs Disorders (WURLDs) among women assembly workers in a multi-national company producing latex products, based in Malaysia. Methods: A sample of 250 respondents have been selected to participate in this study. The methodology employed was developed from the risk management paradigm for the assessment, reduction and prevention of work-related stress. Repetitive work tasks in the factory environment were evaluated using a check list provided by Health and Safety Executive (UK). A questionnaire was designed, based on the information gathered from the focus group discussions and distributed to a sample of all assembly workers available at a particular time. Perception of physical pain was measured using the diagrammatical questionnaire in the form of a mannequin. Well-being was measured using the General Well-being Questionnaire (GWBQ). Pearson Correlation and Linear Regression analyses were used to determine the relationship between workers’ background and the experience of physical pain. Results: Findings from the analyses show that age as well as education background is highly correlated with the experience of worn out hence resulting in report of pain among these workers. Conclusion: The paper exposes the implications of these findings for the design and management of such assembly work in Malaysia.